LUAS PETAK TEBANG OPTIMAL PEMANENAN KAYU DI AREAL HUTAN TANAMAN RAWA GAMBUT - Sona Suhartana; Yuniawati; Dulsalam (BRIN Publishing, 2014)
Skidding, maintenance and canal establisment activities in peat swamp forest require comprehensive planning actionssince the forest has a critical land and difficult to reclamate when it is damaged seriously. It is required to determine anoptimum felling area, considering technical, economical and ecological aspects. A study was carried out in June 2013 atconcession area of Bina Silva Nusa (PT BSN) Company. This study aimed to find out the optimum felling area and theskidding productivity, as well as canal maintenance and establishment. Data were taken descriptively and purposively,which comprised of felling-plot areas (Y) and the costs (X) for skidding, maintenance, and canal establishment. Further,the obtained X-Y data couples were analyzed for possible quadratic regression models. This study resulted model of theoptimum felling area : 1. Y = 55.7 - 6.8 X + 0.21 X ; or Ln Y = 55.7 - 6.8 Ln X + 0.21 Ln X , whichR = 0.1532** or R = 0.391 (R = 0.254), with the optimum felling area (Y ) of 22.21 ha and the minimumcost (X ) as much as Rp 612.644.033; 2. The average increase of skidding productivity andestablishment/maintenance of the secondary canal, collector canal and tertiery canal were 1.37 m /hour (9.5%), 1.298m/hour (5.3%), 1.706 m/hour (2.33%), and 1.4 m/hour (1.3%).